2010
DOI: 10.1075/sll.13.2.02ecc
|View full text |Cite
|
Sign up to set email alerts
|

A formal analysis of phonological contrast and iconicity in sign language handshapes

Abstract: This paper discusses the role of iconicity in sign language phonology by utilizing recently developed tools available in the areas of phonological contrast and feature distribution. In particular, we explain the degree to which iconic elements of handshape interact with the feature system of sign language handshapes in different components of the lexicon, by making specific reference to handshape features that specify joint position. We then discuss similarities and differences between signed languages and spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“… 3 The algebraic account is further challenged by the iconicity of signs (Ormel et al, 2009 ; Eccarius and Brentari, 2010 ; Thompson et al, 2010 ; Brentari, 2011 ), which has been shown to affect their on-line processing by adults (Thompson et al, 2009 , 2010 ), children (Ormel et al, 2009 ) and infants (Thompson et al, 2012 ; but see Emmorey et al, 2004 ; Bosworth and Emmorey, 2010 ). Iconicity implies that the representation of signs is continuous and analog, not discrete and digital, as required by the algebraic proposal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 3 The algebraic account is further challenged by the iconicity of signs (Ormel et al, 2009 ; Eccarius and Brentari, 2010 ; Thompson et al, 2010 ; Brentari, 2011 ), which has been shown to affect their on-line processing by adults (Thompson et al, 2009 , 2010 ), children (Ormel et al, 2009 ) and infants (Thompson et al, 2012 ; but see Emmorey et al, 2004 ; Bosworth and Emmorey, 2010 ). Iconicity implies that the representation of signs is continuous and analog, not discrete and digital, as required by the algebraic proposal.…”
mentioning
confidence: 99%
“…However, the effects of iconicity are not specific to sign language (for a recent review of spoken language, see Schmidtke et al, 2014 ). Moreover, the encoding of phonetic and embodied aspects of signed and spoken words does not preclude the existence of a second format of representation that is algebraic, abstract and fully productive (Brentari, 2007 ; Mahon and Caramazza, 2008 ; Eccarius and Brentari, 2010 ).…”
mentioning
confidence: 99%
“…Handling handshapes tend to be highly analogue and less conventionalized, and the problem that these forms represent for linguistic analyses is how such forms, which may not be completely discrete, can be described (van der Kooij, 2002). Despite the apparent productive and analogue appearance of handling constructions, some researchers have asserted that DCs contain discrete handshapes that function as morphemes (Eccarius & Brentari, 2010; McDonald, 1982; Slobin et al, 2003; Supalla, 1986, 2003; Zwitserlood, 2003). Others have argued against such an analysis because depicting handshapes appear to vary in a non-discrete and analogue fashion (de Matteo, 1977; Mandel, 1977; for further discussion see Schembri, 2003).…”
Section: Introductionmentioning
confidence: 99%